Echocardiographic evaluation including tissue Doppler imaging in New Zealand white rabbits sedated with ketamine and midazolam - Fontes-Sousa AP (2009)
Limited data are available on the use of more recent echocardiographic parameters in the rabbit. Echocardiographic examination, including conventional echocardiography and tissue Doppler imaging (TDI), was performed on 26 male New Zealand white rabbits under ketamine-midazolam sedation. Particular emphasis was placed on the more recent systolic and diastolic parameters, such as myocardial performance index (Tei index) and mitral annular motion (from septal and lateral sides of the left ventricle) obtained using pulsed TDI. Parameters that assessed systolic and diastolic function (fractional shortening, Tei index, and maximal mitral E- and A-wave velocities) were comparable to those reported in the literature for rabbits in the awake state. The less cardiodepressive anaesthetic protocol could offer a good alternative in performing echocardiographic evaluation whenever such caution is necessary. TDI is feasible in healthy rabbits and potentially suitable for the investigation of left ventricle systolic and diastolic function.